Toward Regulatory Effects of Curcumin on Transforming Growth Factor-Beta Across Different Diseases: A Review - Ashrafizadeh, Milad; Zarrabi, Ali; Hushmandi, Kiavash; Zarrin, Vahideh; Moghadam, Ebrahim Rahmani; Hashemi, Farid; Makvandi, Pooyan; Samarghandian, Saeed; Khan, Haroon; Hashemi, Fardin; Najafi, Masoud; Mirzaei, Hamed (Frontiers in Pharmacology, 2020)
Immune response, proliferation, migration and angiogenesis are juts a few of cellular events that are regulated by transforming growth factor- (TGF-) in cells. A number of studies have documented that TGF- undergoes abnormal expression in different diseases, e.g. diabetes, cancer, fibrosis, asthma, arthritis, among others. This has led to great fascination into this signaling pathway and developing agents with modulatory impact on TGF-. Curcumin, a natural-based compound, is obtained from rhizome and roots of turmeric plant. It has a number of pharmacological activities including antioxidant, anti-inflammatory, anti-tumor, anti-diabetes and so on. Noteworthy, it has been demonstrated that curcumin affects different molecular signaling pathways such as Wnt/-catenin, Nrf2, AMPK, MAPK and so on. In the present review, we evaluate the potential of curcumin in regulation of TGF- signaling pathway to corelate it with therapeutic impacts of curcumin. By modulation of TGF- (both upregulation and down-regulation), curcumin ameliorates fibrosis, neurological disorders, liver disease, diabetes and asthma. Besides, curcumin targets TGF- signaling pathway which is capable of suppressing proliferation of tumor cells and invading cancer cells.